Book Vandalism in the Library of the Faculty of Communication Sciences at Padjadjaran University - Gusti Wanda, Delfin; Yusuf, Ariel Mohammad Alief; Prijana, Prijana (Universitas Airlangga, 2024)
Background of the study: The large number of users who use the library collection makes the library vulnerable to misuse of the collection. One form of threat of misuse of collections faced by libraries is damage caused by vandalism. Method: The study adopted a quantitative Pre-Experiment research approach with One Shot case study data analysis, with data collection techniques including observation and documentation. Purpose: This research investigates a case of vandalism of collection books in the Library of the Faculty of Communication Sciences, Padjadjaran University. The purpose of this study is to describe the acts of vandalism that occurred. Findings: 200 vandalized books of various types were found. The findings of this study highlighted various forms of vandalism that occurred on the collection books, such as crossing out, giving special colors, drawing, writing, underlining, and giving special marks. Conclusion: Vandalism of books in libraries is a serious problem that limits the library's ability to provide optimal services and disrupts the absorption of information in higher education. Keywords: Book Vandalism, Pre-Experimental Research, University Library —————————————————————————————————————————————————————————– ABSTRAK Vandalisme Koleksi Buku di Perpustakaan Fakultas Ilmu Komunikasi Universitas Padjadjaran Latar Belakang: Banyaknya pengguna yang menggunakan koleksi perpustakaan membuat perpustakaan rentan terhadap penyalahgunaan koleksi. Salah satu bentuk dari ancaman penyalahgunaan koleksi yang dihadapi perpustakaan adalah kerusakan yang disebabkan oleh vandalisme. Metode: Studi ini mengadopsi pendekatan penelitian Pra Eksperimen kuantitatif dengan analisis data One Shot case study, dengan teknik pengambilan data meliputi observasi dan dokumentasi. Tujuan: Penelitian ini menginvestigasi kasus vandalisme koleksi buku di Perpustakaan Fakultas Ilmu Komunikasi Universitas Padjadjaran. Tujuan dari penelitian ini adalah untuk mendeskripsikan tindakan vandalisme yang terjadi. Temuan: Ditemukan 200 buku yang telah mengalami vandalisme dengan berbagai jenis tipe. Temuan penelitian ini menyoroti berbagai bentuk vandalisme yang terjadi pada koleksi buku di perpustakaan, seperti mencoret, memberi warna khusus, menggambar, menulisi, menggaris bawahi, dan memberi tanda khusus. Kesimpulan: Tindakan vandalisme terhadap buku di perpustakaan merupakan masalah serius yang membatasi kemampuan perpustakaan dalam menyediakan layanan yang optimal dan mengganggu penyerapan informasi di perguruan tinggi. Kata Kunci: Vandalisme Buku, Penelitian Pra-Eksperimental, Perpustakaan Universitas